The Leadership Values of Sorogan Method as the Platform Salaf Islamic Boarding School in Roudlotul Fatihah - Wahid Fathoni; Arif Budi Raharjo (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Learning in pesantren that lasts twenty-four hours indicates that every activity is education for students. Various characteristics such as religiosity, entrepreneurship, and leadership can be formed through existing activities, especially sorogan. The purpose of this study is to describe the application of hidden curriculum pesantren in instilling leadership values in Roudlotul Fatihah Traditional Islamic Boarding School through learning activities in the form of sorogan. This is because research on leadership through hidden curriculum is rarely revealed, in contrast to research on religiosity and entrepreneurship in the pesantren environment. In addition, this research can contribute to the current leadership crisis phenomenon. The author uses qualitative methods in processing data from field research using a phenomenological approach. The process of concluding the previous steps is data condensation and data presentation. The findings of applying hidden curriculum in the Raoudlotul Fatihah Traditional Islamic Boarding School in sorogan activities include the Quran, tools in the form of nahwu and shorof, and books of worship. Activities in pesantren have instilled leadership values in delegation, responsibility, truthfulness, accuracy, and initiation. The end of the study concluded that the hidden curriculum of pesantren has formed students to have leader values without realizing it with all the activities that have been carried out.